2009
DOI: 10.1007/s10865-009-9222-7
|View full text |Cite
|
Sign up to set email alerts
|

Emotional support and gender in people living with HIV: effects on psychological well-being

Abstract: Current research indicates that emotional support is strongly associated with physical and psychological adjustment in persons living with HIV/AIDS. While gender- differences in health and health behaviors of HIV positive patients are well studied, less is known about how men and women living with HIV/AIDS may differentially perceive and integrate support into their lives, and how it subsequently affects their psychological well-being. This cross-sectional study examines how emotional support received from par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
63
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 40 publications
9
63
1
2
Order By: Relevance
“…low socioeconomic status, single/nonmarital status are all related to poorer PWB among PLWH (Asakawa et al 2011). Conversely, research on the role of other sociodemographic data and PWB among this patient group is inconclusive and needs further investigation (Gordillo et al 2009). For example, regarding sex, it is recognized that HIV+ women usually receive lower scores on particular well-being dimension (Cherepanov et al 2011).…”
Section: Among People Living With Hiv (Plwh)mentioning
confidence: 99%
“…low socioeconomic status, single/nonmarital status are all related to poorer PWB among PLWH (Asakawa et al 2011). Conversely, research on the role of other sociodemographic data and PWB among this patient group is inconclusive and needs further investigation (Gordillo et al 2009). For example, regarding sex, it is recognized that HIV+ women usually receive lower scores on particular well-being dimension (Cherepanov et al 2011).…”
Section: Among People Living With Hiv (Plwh)mentioning
confidence: 99%
“…Both HIV-positive men and women have been shown to have psychological distress associated with HIV infection [51,52], and most studies have shown evidence that women usually reported higher psychopathogical symptoms or psycholocical co-morbidity than men [53][54][55]. According to Vosvick and colleagues [5], across multiple samples of PLWHA, it is evident that men and women differ in symptoms, behaviors, and other conditions, which greatly influences well-being.…”
Section: Psychopathological Symptomsmentioning
confidence: 99%
“…We used items included in the Stigma Index for People Living with HIV developed by (UNAIDS, 2008). This Index has been translated into 54 languages, including Spanish, and 45.000 people with HIV from 50 countries have been interviewed (GNP+ et al, 2015). The Perceived Discrimination Scale was composed of seven items and the Self-exclusion scale of five items, rated on a four-point self-report scale (1 = never, 4 = always).…”
Section: Methodsmentioning
confidence: 99%